The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpubh.2020.00444
|View full text |Cite
|
Sign up to set email alerts
|

Considering Interim Interventions to Control COVID-19 Associated Morbidity and Mortality—Perspectives

Abstract: Aims and objectives: The pandemic of COVID-19 is evolving worldwide, and it is associated with high mortality and morbidity. There is a growing need to discuss the elements of a coordinated strategy to control the spread and mitigate the severity of COVID-19. H1N1 and Streptococcus pneumonia vaccines are available. The current analysis was performed to analyze the severity of COVID-19 and influenza (H1N1) vaccination in adults ≥ 65. Also, to correlate the lower respiratory tract infections (LRIs), and influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…This study shows that influenza vaccination may have some protective effect against COVID-19 acquisition, though this result was found only as a synergistic effect for the international dataset and for Italy, but not for the United States, and results of other studies have also been contradictory [ 46 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 61 , 62 , 63 , 64 ]. Notably, however, a protective effect of influenza vaccination against coronaviruses and respiratory viruses has previously been reported: Wolff [ 175 ] found that influenza vaccination in the 2017–2018 influenza season protected against resulted in “virus interference”’ with other respiratory infections, “significantly associated with coronavirus and human metapneumovirus; however, significant protection with vaccination was associated not only with most influenza viruses, but also parainfluenza, RSV, and non-influenza virus coinfections.” [ 175 ] Additionally, pneumococcal and influenza vaccinations have been found to synergize in preventing community-acquired pneumonias [ 139 ].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This study shows that influenza vaccination may have some protective effect against COVID-19 acquisition, though this result was found only as a synergistic effect for the international dataset and for Italy, but not for the United States, and results of other studies have also been contradictory [ 46 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 61 , 62 , 63 , 64 ]. Notably, however, a protective effect of influenza vaccination against coronaviruses and respiratory viruses has previously been reported: Wolff [ 175 ] found that influenza vaccination in the 2017–2018 influenza season protected against resulted in “virus interference”’ with other respiratory infections, “significantly associated with coronavirus and human metapneumovirus; however, significant protection with vaccination was associated not only with most influenza viruses, but also parainfluenza, RSV, and non-influenza virus coinfections.” [ 175 ] Additionally, pneumococcal and influenza vaccinations have been found to synergize in preventing community-acquired pneumonias [ 139 ].…”
Section: Discussioncontrasting
confidence: 57%
“…However, as they note [ 45 ], some of the vaccinations occurred within similar time frames for the patient, so confounding effects were difficult to tease apart. Nonetheless, other population-level studies have also identified COVID-19 protective effects of influenza vaccination [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ] and MMR vaccination [ 56 , 57 , 58 ], or more specifically, rubella vaccination [ 48 ]. Again, except for the Sambul et al [ 48 ] study, data were not controlled for possible confounding effects of receiving multiple vaccines within a similar timeframe, but in several controlled studies, neither MMR (or measles-containing and rubella-containing vaccines) nor influenza vaccine was associated with protection against COVID-19 case or death rates in population-wide studies [ 5 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study examined influenza vaccination data from 34 countries (using Organisation for Economic Cooperation and Development data) with COVID-19 mortality from worldometer data and reported a negative correlation between influenza vaccination status and COVID-19 mortality (R 2 0.338). 17 These studies were limited by the use of aggregated data, however. Two retrospective studies using patient-level data include a large Italian cohort study in which receipt of influenza vaccination was associated with 11% lower odds of COVID-19 diagnosis, and among a subgroup of those aged ≥65 years vaccinated in the first half of the vaccination programme, a 44% and 30% lower odds of hospitalisation and mortality, respectively.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Based on the assumptions, Del Riccio et al [11] conducted a systematic review and found that there was overall no evidence to suggest a negative impact of influenza vaccination on SARS-CoV-2 related infections, illness, or deaths, while some of the included studies even reported significantly inverse associations. Though some of the recent studies have found that influenza vaccine uptake was negatively associated with COVID-19 incidence [12,13], severity [13,14], and mortality [13,15], others showed no evidence of such associations [16][17][18]. Therefore, a systematic review and meta-analysis of the association between influenza vaccination and SARS-CoV-2 infection and its outcomes is needed to provide conclusive evidence.…”
Section: Introductionmentioning
confidence: 99%